Multiplexed immunophenotyping of circulating exosomes on nano-engineered ExoProfile chip towards early diagnosis of cancer - Zhang, Peng (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Circulating exosomes have been studied as a promising biomarker for non-invasive cancer diagnosis, as they are implicated in tumor initiation, progression, and metastasis. However, the clinical significance of circulating exosomes has not been revealed thoroughly, due to the technical limitation in sensitive and multiplexed detection of cargoes on exosomes, such as proteins and nucleic acids. Herein we developed an integrated exosome profiling platform (ExoProfile chip) to afford superior sensitivity and multiplexed capability for quantitative detection of a panel of surface protein markers on exosomes. To achieve this goal, we innovatively constructed 3D porous serpentine nanostructures via patterned colloidal self-assembly to provide enormous reaction sites and improve biosensing efficiency of exosomes. Meanwhile, the switchable microfluidic design enabled the simultaneous detection of eight markers on single addition of exosome samples. The ExoProfile chip was validated with purified exosomes from SKOV3 cells, which yielded a limit of detection of 21 exosomes per μL. We applied the ExoProfile chip to clinical analysis of circulating exosomes using only 10 μL ovarian cancer plasma and completing the analysis within 3 h. The diagnostic power of seven markers (EGFR, HER2, CA125, FRα, CD24, EpCAM, and CD9 plus CD63) were evaluated with receiver operator characteristic curve and heatmap clustering. Compared to single biomarker, the combined assessment of a biomarker panel was demonstrated to display improved accuracy in distinguishing early and late stage cancer. The results suggested the ExoProfile chip as a promising platform for molecular fingerprinting of circulating exosomes towards early cancer diagnosis.